Response of Arabian Sea to the local forcing during 2003 pre-monsoon warming phase - CHOWDARY, J. S.; GNANASEELAN, C.; THOMPSON, BIJOY; SINHA, S. K.; SALVEKAR, P. S. (MAUSAM, 2005)
Prior to the onset of south west monsoon the warmest part of the ocean (SST > 30.5° C) has been observed in the South Eastern Arabian Sea (SEAS). Arabian Sea Monsoon Experiment (ARMEX) provided an excellent opportunity to understand the processes that are associated with the formation of warm pool over SEAS during March and April 2003 and its collapse in June. It is observed that SST over SEAS exceeds 29.5° C, in the weekly SST analysis from ARMEX and Tropical Rainfall Measuring Mission (TRMM) Micro wave Imager (TMI) observations in the last week of March itself. Along with ARMEX and TMI data, Quikscat near surface winds have been used in the study to examine the role of wind driven transport in this region and it was found that at southern boundary (8° N) of the Arabian Sea the transport was southward during southwest monsoon period and northward in the winter monsoon period. In March and April the weak transports and the increase in the insolation over the SEAS are supporting the growing phase of warm pool. The vertical velocity at the bottom of Ekman layer gradually increasing from last week of May 2003 and attains higher value after onset of monsoon, which helps to bring up the cold water and cool the surface. The cooling also is caused by the offshore advection of cold water from Somali coast and high salinity transport from northern Arabian Sea.